Study of prevalence and antimicrobial susceptibility pattern of blood culture isolates from a tertiary care hospital of North India - Nazir, Asifa; Sana, Ifshana; Peerzada, Bushra Yousuf; Farooq, Tabindah (International Journal of Research in Medical Sciences, 2018)
Background: Bacterial bloodstream infections (BSIs) are important causes of morbidity and mortality world-wide. The choice of antimicrobial therapy for bloodstream infections is often empirical and based on the knowledge of local antimicrobial activity profiles of the most common bacteria causing such infections. The objective of the study was to determine the pattern of bacterial isolates from the blood cultures in a teaching hospital and determine their antibiotic resistance and provide guidelines for choosing an effective antibiotic therapy in cases of septicaemia. Methods: The etiological and antimicrobial susceptibility profile of blood cultures over a period of one year at a tertiary care hospital was studied. Blood culture positive isolates were identified by BacT/Alert3D, an automated blood culture system, while as identification of the isolates from these samples and their antimicrobial sensitivity testing was performed with Vitek2 Compact. Results: There were 2231 blood culture samples, of which 565 (25.3%) were identified to be culture positive. Out of 565 positive cultures, 447 (79.1%) showed bacterial growth; Gram positive were 306 (54.2%) and Gram negative were 141 (24.9%). Candida species were isolated from 118 (20.9%) of positive samples. The most frequently identified Gram-positive bacteria were Coagulase-negative staphylococci 208 (67.9%) and the most common Gram-negative isolates were Acinetobacter species 89 (63.1%). The most sensitive drugs for gram-positive isolates were vancomycin, and linezolid while as gram-negative isolates showed 100% sensitivity to colistin and tigecycline. Conclusions: This study reveals a significant prevalence of bacterial isolates in blood and it highlights the need for periodic surveillance of etiologic agent and antibiotic susceptibility to prevent further emergence and spread of resistant bacterial pathogens.